Practical approaches to the diagnosis of osteoarthritis - P. O. Vovchuk (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Osteoarthritis is a common chronic joint disease in dogs, characterized by the progressive development of pain, lameness, and a significant reduction in activity, which significantly impacts the quality of life of the affected animals. This disease develops gradually and can have various etiological factors, including trauma, genetic disorders, dysplasia, and obesity. Osteoarthritis is accompanied by changes in the osteochondral complex, including alterations in cartilage tissue, subchondral bone, synovial membrane, and periarticular structures. These pathological changes complicate the diagnosis of the disease and require the use of modern imaging techniques and laboratory tests. The application of contemporary diagnostic methods enhances the accuracy of osteoarthritis diagnosis and allows for detecting the disease at early stages. In particular, the Canine Osteoarthritis Staging Tool (COAST) should be noted, which includes a comprehensive approach to assessing the condition of the animal, encompassing both clinical symptoms and radiological changes. Radiography remains the primary imaging method, but its sensitivity at early stages is insufficient, limiting its use in detecting initial joint changes. Magnetic resonance imaging and computed tomography are more precise imaging methods that allow for detecting small osteophytes, subchondral changes, and other pathological processes that cannot be visualized using radiography. In addition to imaging methods, synovial fluid analysis plays a crucial role in diagnosing osteoarthritis, as it identifies inflammatory processes in the joints. Specifically, the assessment of inflammation biomarkers, such as C-reactive protein and hyaluronic acid, can be helpful in differentiating osteoarthritis from other inflammatory joint diseases. Despite significant progress in diagnosing osteoarthritis in dogs, certain limitations remain, related to the high cost and limited availability of modern imaging methods and biomarker analysis. This necessitates further research to improve early detection methods of osteoarthritis and to optimize treatment strategies, which will help improve the prognosis and quality of life for animals with this disease.